Preparation and evaluation of polymer microspheres for enhanced lateral flow immunoassay: the case study for malaria - Hobbs, Henriëtte Renée (Institute of Infectious Disease and Molecular Medicine, 2021)
We proposed that the development of a new high capacity polymer microsphere technology, termed ReSyn, could be developed as viable detection reagents for lateral flow technology. This body of work outlines the development of this new high capacity polymer microsphere technology for suitability to flow on lateral flow membranes, and highly specific biomarker detection for immunoassay development. Proof-of-concept was achieved using hCG (pregnancy biomarker) and validated for detection of pLDH and HRP2 as biomarkers of malaria. The sensitivity, stability and multiplex capability of these microspheres were further explored and compared against the current ‘gold' standard detection agent for lateral flow, colloidal gold. Malaria was selected as a suitable target for evaluation of the microsphere technology since it is considered to be a global epidemic that can benefit greatly from improved point-of-care diagnostics. Malaria affects almost half of the world's population and is responsible for causing approximately 655 000 deaths per annum in 2010, with 90% of these deaths occurring in Africa and 85% of these deaths occurring in children under 5 years of age (del Prado et al., 2014; Kokwaro, 2009; White et al., 2014; WHO, 2009). Febrile disease diagnosis at point-of-care is often based on symptomatic diagnosis rather than on the use of validated diagnostic technologies, and is considered one of the major contributing factors for the high morbidity and mortality rate of malaria (Chandler et al., 2008; Kain et al., 1998; Kokwaro, 2009). Improved diagnostic technologies, allowing for sensitive and accurate diagnosis at the point-of-care, could assist alleviating these problems through the improved management of disease (Bell et al., 2006). Lateral flow rapid diagnostic tests are the preferred method for point-of-care diagnostics in resource constrained areas but have several limitations including sensitivity and stability in resource constrained settings (Bell et al., 2006). Improvements in detection agents are seen as a viable approach to improving these features of diagnostic assays. The results of this study show that the polymer microspheres provide improved stability to immobilised antibodies, with potential for translation into improved stability for diagnostic assays in tropical malaria endemic regions. The polymer microspheres offered high specificity and comparable visual sensitivity to the market leader colloidal gold and is therefore considered as alternate detector agents in lateral flow assays. Additionally, the microspheres can be dyed various colours (red and blue in this study), allowing for specific and sensitive multiplex detection of multiple analytes in a single sample. This increases the versatility of the microspheres for lateral flow diagnostic application, and improves the interpretation of lateral flow diagnostic technology at the point-of-care.